Sertifikat Laik Fungsi pada Bangunan Gedung di Kota Bandung Dalam Kaitannya dengan Izin Mendirikan Bangunan - Devi Elora (Universitas Batanghari Jambi, 2021)
The rise of buildings in the city of Bandung is a symbol of the development of the city of Bandung itself, but the development of a city must of course refer to the existing rules. The existence of buildings whose utilization is often found to be inconsistent with IMB, in other words, there is a mismatch between SLF and IMB which of course raises problems regarding the use of building functions that are not in accordance with existing building permits. Identification of the problem in this thesis research is how the legal arrangements regarding SLF for buildings are in the presence of an IMB and how is the SLF for buildings that are not used in accordance with the IMB. The research method uses the normative juridical method, which is carried out using library research and field research conducted at institutions related to the issue of building function worthiness certificates in the city of Bandung in relation to building permits. The conclusion obtained in this study is the legal arrangement regarding SLF for buildings in the presence of an IMB which is basically the existence of an SLF located or based on an IMB. SLF is a provision for the use of buildings, while IMB is the legality of the existence of buildings, problems regarding the incompatibility between IMB and SLF can be studied from 3 main subjects of the existence of SLF namely government, society and the rule of law, but what is fundamental is the absence of legal rules regarding specific implementation instructions in The City of Bandung regulates SLF, so that SLF in Bandung City has not been able to run well. SLF of buildings whose utilization is not in accordance with the IMB has the consequence that the use of the SLF that should be in accordance with the IMB must be adjusted to the provisions contained in the IMB.